Perspektif Jual Beli Online dalam Perspektif Hukum Islam dan KUHPerdata - Fajarwati Kusuma Adi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
The online shop business is a business that is rife in the current era, in addition to facilitating buying and selling, it also makes it easier for long distances to become close. Transactions become more accessible. This is done in accordance with Islamic law, namely the Al-Quran and Hadith and must be adjusted to State Law, especially in accordance with the applicable laws and regulations, namely in accordance with the Civil Code Article 1457 and Article 1458. Due to this basis, it is expected that sellers and the buyer conducts the sale and purchase transaction properly and in accordance with the applicable rules. Fraud and fraud can also be minimized. Sales can be done without distance constraints and purchases are also safer. The method used in this research is quantitative method / library (library research) with supporting data from books, internet and journals for data collection and data analysis. So that with this writing, the public is expected to be able to choose a real online store with merchandise that is not fraudulent and all risks can be communicated to the seller. In official online stores, there is usually an online store address that contains tracking data so that returns can be made if there are product defects.